Breast Cancer Prevention through SADARI Intervention in Women of Reproductive Age in Loa Bakung - Nurachma, Evy; Samsiah, Samsiah; Imelda, Fara (Interdisciplinary Social Studies, 2022)
Background: Cancer is a non-communicable illness brought on by the unnatural and unchecked proliferation of bodily tissue cells. A malignant tumor of the breast or one of the breasts is breast cancer in and of itself. Aim: The purpose of this activity is to educate through BSE (Breast Self-Examination, SADARI) socialization as the first step in preventing breast cancer and increasing the participation of the community, especially women of reproductive age, in carrying out early detection of breast cancer prevention. Method: To delve further into this subject, the researchers adopted a qualitative technique. The researchers sought to learn more about residents' awareness about breast cancer and its prevention, particularly SADARI, by initial observation and interviews. The researchers analyzed and organized the data they had gathered in order to come up with a reliable conclusion. Findings: In terms of knowledge, before being given health education by Posyandu (Integrated Healthcare Center, Pos Pelayanan Terpadu) cadres most of the knowledge of women of reproductive age about SADARI was in the sufficient category as many as 18 respondents (45.%) and after being given health education there was an increase where most of the women of reproductive age’s knowledge (80%) became good. Meanwhile, for the attitude before being given health education by Posyandu cadres, some of women of reproductive age had a negative attitude towards SADARI (12.5%), and after being given There was an increase in health education by cadres, namely the majority of respondents 39 respondents (97%) had a positive attitude towards SADARI.